Strategi Komunikasi Kementerian Pemberdayaan Perempuan Dan Perlindungan Anak (Kemenpppa) Dalam Menanggapi Kasus Sinetron Suara Hati Istri : Zahra - hanny novita; Ahmad Junaidi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
With the development of technology, people's lives cannot be separated from the mass media. Television is one of them, television has a major influence on the development of society, especially in association. Soap operas that are liked by many people, one of which is the soap opera entitled